Expert Validation of the Herbarium Collection Based on Selapanan Bayi Traditional Ceremony - Vivi Haryani; Mucharommah Sartika Ami (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The integration of local wisdom, especially the Selapanan Bayi traditional ceremony, in the development of biology learning media has never been done. Through this research, biology learning media was developed in the form of a herbarium collection with plant specimens used were the types of plants used in the Selapanan Bayi traditional ceremony in Jombang Regency. The purpose of this study was to determine the results of the validation of herbarium expert and learning media expert on the products developed. This research is a type of research and development that refers to the R&D model, which consists of 10 stages. Only the first five stages were carried out in this study namely potential and problems, data collection, product design, design validation, and design revision. The instruments used were interview guide, herbarium expert validation sheet, and learning media expert validation sheet. The collected data were analyzed descriptively. The results of the herbarium expert’s validation of the developed product showed a value of 80 with the criteria quite feasible. As for the results of the expert validation of learning media, it shows a value of 95 with very feasible criteria. This indicates that the herbarium collection developed can be used as a biology learning media, especially for Plantae Kingdom material.